(untitled) (Fiep Bulletin - online, 2011)
Given the existing highly competitive in today’s high performance sport, we are faced with various aspects of the complexity of the athlete that should be taken into account to achieve peak performance. The nutrition and exercise physiology are a natural link. Proper nutrition is the foundation for physical performance, and provides the fuel for biological work and the chemicals to extract and use the potential energy in this fuel. The sources of vegetarian protein are mostly associated with carbohydrate and non vegetarian associated with fats, so it is expected that people who adopt a vegetarian diet have a higher amount of essential substrate for endurance exercise, carbohydrate.This study is to contribute to the scientific community, coaches and athletes on nutritional aspects most favorable to achieve the desired performance and help clarify the questions about the influence of vegetarian and non vegetarian diets in the performance of triathletes, analyzing the data of VO 2 maximum, using field test. Participants were 4 athletes of the "Ironman" held in Florianopolis in 2007 (34.75 ± 8.42 years, 76.5 ± 8.19 kg body weight, 1.75 ± 0.05 m in height) , 2 elite male and 2 category M 4044 (male between 40 and 44 years) Of these, one in each category was classified as vegetarian. There was no significant difference (p <0.05) in aerobic performance related to vegetarian diets (65.50 ± 3.01 mlO 2 / kg / min VO 2 max) and non vegetarian (64.17 ± 1.90 mlO 2 / kg / min VO 2 max) A vegetarian diet is not associated with better endurance performance, but other benefits of this type of diet should be taken into account by the athletes. The vegetarian diet, if well structured and varied supplies all the nutritional needs of the athlete and not affect your aerobic performance.